Mitochondrial and nuclear gene sequencing confirms the presence of the invasive sea anemone Diadumene lineata (Verrill, 1869) (Cnidaria: Actiniaria) in Argentina - Ricardo González Muñoz; Daniel Lauretta; María Cielo Bazterrica; Francisco Alejandro Puente Tapia; Agustín Garese; Gregorio Bigatti; Pablo E. Penchaszadeh; Betina Lomovasky; Fabián H. Acuña (PeerJ, 2023)
Background Diadumene lineata is one of the most widespread sea anemone species worldwide. Although this species has been reported a few times on the Argentine coast since 2004, its identification has traditionally been based on external morphological characteristics, and in most cases no voucher specimens are available to support previous records. Methods In this study, we obtained DNA sequences of two mitochondrial markers (12S and 16S) and two nuclear markers (18S and 28S) from specimens of D. lineata collected in two locations on the Argentine coast separated by almost 800 km. Additionally, we conducted an analysis of the morphology, as well as the types and size ranges of cnidae, using specimens collected at three different locations along the Argentine coast. Furthermore, since introduced populations of D. lineata are presumably ephemeral and only reproduce asexually outside their native range, we examined the internal anatomy of representatives from the Argentine coast for gametogenic tissue as an indication of whether they might be capable of sexual reproduction. Results DNA data support our morphological identification, including cnidae analyses, of the specimens as D. lineata. Furthermore, all specimens examined were determined to be sterile. Discussion Genetic sequence comparisons, phylogenetic reconstruction, and cnidae data support the identification of individuals of D. lineata from Mar Chiquita and Garipe Beach, confirming the presence of the species on the Argentine coast using both morphological and molecular tools. The absence of fertile specimens suggests that each sampled population is likely reproducing only by asexual reproduction and possibly composed of clones. The presence of an additional category of longer p-mastigophores B2a in the actinopharynx and filaments, as well as holotrichs in the column, is also reported. Conclusions For the first time, we have confirmed the presence of D. lineata in Argentina through molecular data. Additionally, our findings indicate that the analyzed specimens are sterile, suggesting that this species is not engaging in sexual reproduction in the studied localities. It is crucial to continue monitoring the populations of D. lineata along the Argentine coast to assess whether they establish sexual reproduction, expand their distribution range or disappear, or potentially cause any harm to local species or alterations in benthic communities.